ANALISIS IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 33 TAHUN 2012 TENTANG PEMBERIAN AIR SUSU IBU EKSKLUSIF (Studi di Kecamatan Arga Makmur Kabupaten Bengkulu Utara) - Dolly Erlian Khevabeta (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
This study shows that in the implementation of Government Regulation No. 33 Year 2012, the Department of Health always educate health workers in health centers especially midwives about exclusive breastfeeding. This information is passed through the village midwife to the community outreach exclusive breastfeeding and pregnant women. In implementing the Government Regulation No. 33 of 2012 the Department of Health do not have sufficient human and financial resources, while for facilities and material information is already available. Midwives in health centers and village midwives have to implement the commitments well in delivering the program to the public especially exclusive breastfeeding mothers with babies. PHC Arga Makmur already cooperating across sectors and programs to support exclusive breastfeeding programs in Arga Makmur subdistrict. Mothers already know and understand about exclusive breastfeeding and its benefits after being given counseling by midwives Conclusion of research is the implementation of Government Regulation No. 33 Year 2012 on Provision of BMS Exclusive in District Arga Makmur review of aspects of communication, resources, implementing and bureaucracy already done PHC Arga Makmur and mothers already understand about exclusive breastfeeding and its benefits after being given counseling by midwives about exclusive breastfeeding. Keywords : Implementation, Government Regulation, Exclusive Breastfeeding